Glioblastoma epigenome profiling identifies SOX10 as a master regulator of molecular tumour subtype - Wu, Yonghe; Fletcher, Michael; Gu, Zuguang; Wang, Qi; Costa, Barbara; Bertoni, Anna; Man, Ka-Hou; Schlotter, Magdalena; Felsberg, Jörg; Mangei, Jasmin; Barbus, Martje; Gaupel, Ann-Christin; et al. (Nature Communications, 2020)
Glioblastoma frequently exhibits therapy-associated subtype transitions to mesenchymal phenotypes with adverse prognosis. Here, we perform multi-omic profiling of 60 glioblastoma primary tumours and use orthogonal analysis of chromatin and RNA-derived gene regulatory networks to identify 38 subtype master regulators, whose cell population-specific activities we further map in published single-cell RNA sequencing data. These analyses identify the oligodendrocyte precursor marker and chromatin modifier SOX10 as a master regulator in RTK I-subtype tumours. In vitro functional studies demonstrate that SOX10 loss causes a subtype switch analogous to the proneural-mesenchymal transition observed in patients at the transcriptomic, epigenetic and phenotypic levels. SOX10 repression in an in vivo syngeneic graft glioblastoma mouse model results in increased tumour invasion, immune cell infiltration and significantly reduced survival, reminiscent of progressive human glioblastoma. These results identify SOX10 as a bona fide master regulator of the RTK I subtype, with both tumour cell-intrinsic and microenvironmental effects.
Gesehen am 17.04.2022